HUMAN CAPITAL DEVELOPMENT MANAGEMENT UNDER DEMOGRAPHIC CHANGE CONDITIONS - Lukianykhin, Vadym; Lukianykhina, Olena; Andrieiev, Andriy (Public Management and Policy, 2026)
The article examines the problem of human capital development management under conditions of demographic change, characterized by population decline, workforce ageing, and intensified migration processes. The relevance of the study is determined by the need to adapt management approaches to new structural constraints of the labor market and to ensure sustainable economic development. The purpose of the study is to substantiate the theoretical and methodological foundations of human capital development management in the context of demographic transformations and to develop a conceptual model of its adaptive reproduction, taking into account structural changes in the labor market. The research is based on generalization, comparative analysis, a structural-functional approach, and elements of statistical analysis of demographic indicators. The economic essence and structural characteristics of human capital have been examined, and the influence of demographic changes on its formation, reproduction, and utilization processes has been identified. Modern approaches and tools of human capital management have been generalized, and the necessity of their integration into a coherent system aimed at enhancing adaptability has been substantiated. It has been found that the key problems include the mismatch between the structure of workforce training and the needs of the economy, the narrowing of the demographic base for human capital formation, increasing regional disparities, and the inefficient use of available labor potential. It has been proven that traditional management approaches are insufficient to respond adequately to demographic challenges and require transformation toward predictive and adaptive models. As a result of the study, a conceptual model of human capital development management has been developed, based on the integration of demographic analysis, forecasting of competency needs, and adaptation of work organization. A step-by-step logic for its implementation has been proposed, ensuring the alignment of human capital parameters with the dynamics of the economic environment. It has been concluded that the implementation of the proposed model will contribute to improving the efficiency of human capital utilization, reducing structural imbalances, and forming a sustainable system of its reproduction. Prospects for further research include the improvement of quantitative assessment methods, the development of forecasting tools, and the study of the impact of digitalization and migration processes on the long-term sustainability of human capital.